Icebreaking polar class research vessels: New Antarctic fleet capabilities - Rogan-Finnemore, Michelle; Ojeda, Miguel; Paz Acosta, Jorge Manuel; Bretel, Patrice; Browne, Nick; Flått, Stig; Shuoren, Wang; Sliester, Randolph (Polar Record, 2021)
Supporting Antarctic scientific investigation is the job of the national Antarctic programmes, the government entities charged with delivering their countries’ Antarctic research strategies. This requires sustained investment in people, innovative technologies, Antarctic infrastructures, and vessels with icebreaking capabilities. The recent endorsement of the International Maritime Organization (IMO) Polar Code (2015) means that countries must address challenges related to an ageing icebreaking vessel fleet. Many countries have recently invested in and begun, or completed, builds on new icebreaking Polar research vessels. These vessels incorporate innovative technologies to increase fuel efficiency, to reduce noise output, and to address ways to protect the Antarctic environment in their design. This paper is a result of a Council of Managers of National Antarctic Programs (COMNAP) project on new vessel builds which began in 2018. It considers the recent vessel builds of Australia’s RSV Nuyina, China’s MV Xue Long 2, France’s L’Astrolabe, Norway’s RV Kronprins Haakon, Peru’s BAP Carrasco, and the United Kingdom’s RRS Sir David Attenborough. The paper provides examples of purposeful consideration of science support requirements and environmental sustainability in vessel designs and operations.
Keywords: Sørishavet; skipsfart; teknologi

Thorbryn - en hvalbåts videverdige karriere - Basberg, Bjørn L (Norsk maritimt museum. Årbok, 2014)
Keywords: Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

Døde menn vender tilbake: Shackletons høyst private Whitbread-seilas - Winge, Jon (Norsk sjøfartsmuseum. Årbok, 1998)
Keywords: Endurance (skip); Ernest Henry Shackleton; Sørishavet; ekspedisjoner; oppdagelsesreiser; skipsfart

Motortankskipenes inntog. En komparasjon av utviklingen i dansk, norsk og svensk skipsbyggingsindustri, ca. 1912 til 1933 - Basberg, Bjørn L (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1986)
Keywords: Sørishavet; historie; hvalbåter; hvalfangstindustri; pelagisk; skipsbyggerier; skipsfart

Bergens deltakelse i den moderne hvalfangst - Tønnessen, Johan Nicolay (Sjøfartshistorisk årbok : Norwegian yearbook of maritime history, 1973)
Keywords: Antarktis; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; skipsfart